Development of A Trilingual E-Dictionary for Early Childhood; Indonesia-English-Lampung - Septiyana, Linda; Aneka, Aneka; Mandasari, Berlinda; Ramadhan, Fezka Shella Syafari (Tapis: Jurnal Penelitian Ilmiah, 2023)
The development of this trilingual e-dictionary (Indonesian-English-Lampung) is expected to help children learn multi-languages and make it easier for children to learn Indonesian, English, and Lampung language. This study aimed to develop a trilingual e-dictionary (Indonesia-English-Lampung) for early childhood students’ at TK Pertiwi Metro. The study used a Research and Development approach, where the data were collected through questionnaire and interview. Qualitative data were analyzed using interactive analysis and quantitative data analysis used percentages. The research participants consisted of 25 Kindergarten teachers at TK Pertiwi Metro and TK PKK 1 Yosodadi Metro. The results showed that learning media in the form of e-dictionary is very needed to introduce languages to early childhood. The contents of trilingual e-dictionary consists of three volumes. Volume one consists of five themes: numbers, colors, fruits, vegetables, and animals. Volume two consists of four themes: family, human body, transportation, and profession. Volume three consists of four themes: classroom, bedroom, nature, and time. The total vocabulary of the entire volume is 158 vocabularies. Furthermore, the teachers’ responses toward the trilingual e-dictionary (Indonesia-English-Lampung) showed that 0% expressed disagreed, 10% less agreed, 41% agreed, and 49% strongly agreed. The average score is 3,38 and, if converted on a table with a scale of 4, includes into a very good category. Therefore, a trilingual e-dictionary (Indonesia-English-Lampung) is declared suitable to be used as an interactive media in learning languages for early childhood.